GEOPOLITICAL RISK AND MACROECONOMIC VARIABLES ON RUPIAH EXCHANGE RATE DYNAMICS IN INDONESIA: EVIDENCE FROM 2020-2025 - Meuthia Nurul Soraya; Dede Ruslan; Eko Wahyu Nugrahadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study analyzes the effect of geopolitical risk and macroeconomic variables on the dynamics of the rupiah exchange rate in Indonesia during 2020-2025. The variables comprise the rupiah exchange rate, geopolitical risk, inflation, interest rate, world oil price, and foreign exchange reserves. Monthly secondary data were examined using the Vector Error Correction Model (VECM), supported by the Phillips-Perron unit root test, optimal lag selection, VAR stability test, Johansen cointegration test, Impulse Response Function (IRF), Forecast Error Variance Decomposition (FEVD), and Block Exogeneity Wald Test. The findings show two cointegrating relationships, indicating a long-run equilibrium among the variables. In the short run, geopolitical risk significantly affects rupiah exchange rate dynamics. In the long run, inflation, interest rate, world oil price, and foreign exchange reserves are associated with the rupiah exchange rate. IRF results indicate that geopolitical risk shocks initially generate a negative response, then a positive response, before gradually stabilizing. FEVD results show that in the tenth period, rupiah exchange rate variation is mainly explained by its own shock (71.52%), followed by geopolitical risk (14.01%) and world oil price (12.81%).